SNP markers applied to the characterization of Spanish tomato (Solanum lycopersicum L.) landraces - Cortes-Olmos, Carles; Vilanova, S.; Pascual, L.; Roselló, Josep; Cebolla-Cornejo, Jaime (2017)
The variability present in 63 accessions of 14 Spanish tomato (Solanum lycopersicum L.) landraces has been studied using morpho-agronomical descriptors and molecular markers. For this purpose, a set of 32 polymorphic SNP has been specifically developed. The relation between Spanish landraces has been analysed using the information generated. The cluster analysis using SNP data showed a moderate correlation with morpho-agronomical data, which is rare considering the low level of genetic diversity found in tomato and that few genes control key traits in landrace recognition, as size, shape and external appearance. Compared with previous studies, the set of SNP markers used provides a reliable tool for the analysis of diversity, with high bootstrap values obtained in the cluster analysis. Nevertheless, it seems to exist a strong influence of the specific combination of populations of each landraces analysed, the marker type and set of markers on the analysis of genetic differentiation in tomato landraces. Specific combinations of SNP markers (from two to six markers per landrace) enabled the clear identification of most of the landraces evaluated. Its use would be a useful tool to control the commercial fraud typical of quality niche markets where high yielding modern varieties resembling traditional landraces are sold, taking advantage of the price premium of these materials. (C) 2015 Elsevier B.V. All rights reserved.